Dynamic inefficiency and fiscal interventions in an economy with land and transaction costs - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2020)
The paper contributes to the discussion on whether real interest rates smaller than real growth rates can be taken as evidence of dynamic in- efficiency that calls forfiscal interventions. A seemingly killing objection points to the presence of land, a non-produced durable asset whose value becomes arbitrarily large as interest rates go to zero. Such an asset, it is claimed, can accommodate any need for a store of value at interest rates above growth rates, so dynamic inefficiency cannot arise. The paper shows that this objection is not robust to the presence of an arbitrarily small per-unit-of-value transaction cost. The paper also gives conditions under whichfiscal interventions provide for Pareto improvements even though the interventions themselves are also costly.
hdl:21.11116/0000-0005-E12F-9
Keywords: D15; D61; E21; E62; H63; 330; Dynamic inefficiency; fiscal policy; public debt; overlapping-generations models with land; transaction costs; pay-as-you-go retirement provision